(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
In this paper two-dimensional differential quadrature method has been used to analyze thick Functionally Graded (FG) rotating disks with non-uniform boundary conditions and variable thickness. Material properties vary continuously along both radial and axial directions by a power law pattern. Three-dimensional solid mechanics theory is employed to formulate the axisymmetric problem as a second order system of partial differential equations. The non-uniform boundary conditions are exerted directly into the governing equations to reach the eigenvalue system of equations. Four different disk profile shapes are considered and discussed. The effect of the power law exponent is also investigated and results show that by the use of material which functionally varied along the radial and especially axial directions the stresses and strains can be controlled so the capability of the disk is increased. Comparison with other available approaches in the literature shows a good agreement here in terms of computational time, robustness and accuracy of the present method. Moreover, novel applications are shown to provide results for further studies on the same topics.